Psicologia nos negócios internacionais - Moraes, Joanna Passos de (My University, 2024)
The present work has as its theme the psychology in interactional business, to point out as its main objective to help, strengthen and understand psychology in the professional context in the area of international negotiations, through the vision of negotiation of traders on a daily basis with other ethnicities and cultures, demonstrating through these relationships the importance of techniques, improvement and perception of the psychological languages that follow the analysis and perfection of It is evident the importance of maintaining a good relationship with the various cultures, and the fact that this directly reflects in the good progress of the negotiations and success of the company. To this end, the study showed as specific objectives of the work the importance of negotiation knowledge and psychology in interpersonal relationships, exploring in depth each objective. [resumo fornecido pelo autor]
O presente trabalho tem como tema a Psicologia nos negócios internacionais, e apontar como objetivo principal ajudar, fortalecer e compreender a psicologia no âmbito profissional na área das negociações internacionais, através da visão de negociação dos trader no dia a dia com outras etnias e culturas, demonstrando através desses relacionamentos a importância de técnicas, aprimoramento e percepção das linguagens psicológicas que sucedem a análise e perfeição de uma negociação. Sendo evidente a importância em se manter um bom relacionamento com as diversas culturas, é fato que isso reflete diretamente no bom andamento das negociações e sucesso da empresa. Para tanto, o estudo evidenciou como objetivos específicos do trabalho a importância dos conhecimentos de negociação e a psicologia nos relacionamentos interpessoais, explorando a fundo cada objetivo. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Negócios - Aspectos psicológicos